Do Improvements in Balance Relate to Improvements in Long-Distance Walking Function after Stroke? - Louis N. Awad; Darcy S. Reisman; Stuart A. Binder-Macleod (Stroke Research and Treatment)
Stroke survivors identify a reduced capacity to walk farther distances as a factor limiting their engagement at home and in community. Previous observational studies have shown that measures of balance ability and balance self-efficacy are strong predictors of long-distance walking function after stroke. Consequently, recommendations to target balance during rehabilitation have been put forth. The purpose of this study was to determine if the changes in balance and long-distance walking function observed following a 12-week poststroke walking rehabilitation program were related. For thirty-one subjects with hemiparesis after stroke, this investigation explored the cross-sectional (i.e., before training) and longitudinal (i.e., changes due to intervention) relationships between measures of standing balance, walking balance, and balance self-efficacy versus long-distance walking function as measured via the 6-minute walk test (6MWT). A regression model containing all three balance variables accounted for 60.8% of the variance in 6MWT performance (R2=.584; F(3,27)=13.931; P<.001); however, only dynamic balance (FGA) was an independent predictor (β=.502) of 6MWT distance. Interestingly, changes in balance were unrelated to changes in the distance walked (each correlation coefficient <.17, P>.05). For persons after stroke similar to those studied, improving balance may not be sufficient to improve long-distance walking function.